A Learning Climate that Supports Autonomy as a Driver of Students’ Self-Efficacy in Economics Learning - Imey Indayanti Ensar; Eeng Ahman; Yana Rohmana (MASI Mandiri Edukasi, 2026)
In the learning process, students’ beliefs in their own abilities do not form spontaneously; instead, they develop through experiences shaped by classroom dynamics and the quality of pedagogical interaction. Low self-efficacy is often a major obstacle to economic learning, especially when students encounter material that requires conceptual analysis and numerical skills. To understand how such self-beliefs are constructed in real classroom contexts, this study explores students’ subjective experiences of interpreting an autonomy-supportive learning climate and how this climate strengthens their self-efficacy. The research employed a qualitative approach using an Interpretative Phenomenological Analysis (IPA) design and involved six grade XI social science students selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and documentation, and were analyzed following IPA procedures. The findings generated four key themes: (1) teacher-provided autonomy that fosters confidence through opportunities for student choice; (2) verbal encouragement that helps students interpret their abilities positively; (3) small mastery experiences that serve as internal validation of competence; and (4) a positive classroom atmosphere that provides psychological safety for active participation and exploration. These results emphasize that self-efficacy development is a socio-psychological process influenced by emotional states, interpersonal support, and meaningful learning experiences. The study highlights the importance of creating a learning climate responsive to students’ psychological needs as an effective pedagogical strategy for enhancing self-efficacy in economics learning.